Effects of chronic exposure to hexavalent chromium in water on oxidative stress parameters in Wistar rats - Machado, Aline Belem; Caprara, Juliana Foresti; Franceschi, Itiane Diehl de; Linden, Rafael; Berlese, Daiane Bolzan; Feksa, Luciane Rosa (Acta Scientiarum. Biological Sciences, 2019)
Hexavalent chromium [Cr (VI)] is a metal utilized in different industries and consequently disposed in the environment. It is a toxic substance and its reduction to trivalent Cr [Cr (III)] generates intermediates, which are responsible for the oxidation of molecules, and cause the oxidative stress. Therefore, the aim of this study was to evaluate if Cr (VI) could induce oxidative stress in Wistar rats. In this study, Wistar rats were chronically exposed to 25 and 50 ppm of potassium dichromate in drinking water for 30 days. The levels of Cr were evaluated in the blood and tissues (liver, kidneys, and lungs). Oxidative stress was determined in the liver, kidneys, and lungs and was evaluated by DFCH, TBA-RS and carbonyl test. Antioxidant enzymes were evaluated through catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities. Regarding the results, Cr concentration was significantly elevated in all tissues, however, it was lower in the lungs. In relation to the oxidative stress parameters, there was a significant increase of DCFH levels in the kidneys and carbonyls in liver and kidneys. Regarding the antioxidant enzymes, SOD was decreased in all organs and GPx was diminished in the kidneys. These data indicated that Cr (VI) could induce oxidative stress in the kidneys and liver due to an imbalance between oxidative and antioxidant parameters. The lungs were little affected, possibly by the lowest chromium accumulation.